Ammonia loss, ammonium and nitrate accumulation from mixing urea with zeolite and peat soil water under waterlogged condition - Omar, Latifah; Ahmed, Osumanu Haruna; Nik Ab. Majid, Nik Muhamad (Academic Journals, 2011)
Ammonia loss from urea significantly hinders efficient use of urea in agriculture. In order to reduce ammonia loss and, at the same time, improve beneficial accumulation of soil exchangeable ammonium and nitrate for efficient utilization by plants, this laboratory study was conducted to determine the effect of mixing urea with zeolite and peat soil water on ammonia volatilization, soil exchangeable ammonium and available nitrate contents, compared with urea without additives under waterlogged condition. The soil used was Bekenu Series (Fine loamy, siliceous, isohyperthermic, red-yellow to yellow Tipik Tualemkuts). The mixtures significantly reduced ammonia loss by 25 to 38% compared with urea (straight urea, 46% N). All the mixtures of zeolite and peat soil water with urea significantly increased soil exchangeable ammonium (by 59 to 80 mg kg -1) and available nitrate (by 5 to 12 mg kg -1) contents. The temporary reduction of soil pH may have retarded urea hydrolysis. It could be possible to improve the efficiency of urea surface-applied to high value crops by addition of zeolite and peat soil water.